280 Cognitive dysfunction in AI-CTD is associated with traditional cardiovascular risk factors but not immunological parameters. (April 2019) - Zamora, Marta Aguilar; Dutton, Katie; Wigston, Zoe; Alase, Adewonuola; Psarras, Antonios; Md Yusof, Md Yuzaiful; Vital, Edward
Abstract : Background: Cognitive dysfunction is a common problem in autoimmune connective tissue diseases such as SLE that can be screened for using the Montreal Cognitive Assessment (MoCA). The causes of cognitive dysfunction are poorly understood. They may include immune-mediated neurological dysfunction (which should be targeted using immunosuppression) or traditional cardiovascular risk factors (which may be treated as in non-SLE patients). The purpose of this study was to explore these counter-hypotheses in patients with established autoimmune disease by analysing conventional measures of autoimmunity, cardiovascular risk, as well as validated scores for interferon status. Since cumulative organ damage and toxicity of therapy may affect these patients, we also included a cohort of At Risk individuals as previously described. 1 Methods: We assessed three cohorts: (1) patients with established AI-CTD (SLE, Sjogrens syndrome or undifferentiated CTD >12 months); (2) at risk individuals referred to secondary care due to ANA +and symptoms suggestive of AI-CTD less than 12 months duration; (3) age and sex matched healthy controls. Cognitive dysfunction was tested using the MoCA. Cardiovascular risk was assessed by recording diabetes, hypertension, previous angina or AMI, atrial fibrillation and cholesterol. Type I interferon activity was assessed using a validated two-score system for IFN status previously described. 2 Results: As expected, the number of patients with an abnormal MOCA score was greater in AI-CTD and At-Risk individuals than in the healthy controls (HC: 20%; At Risk: 39%; SLE: 34%). Also as expected, the IFN scores varied significantly between these groups (p=0.046, F=4.66). We compared parameters between individuals with normal and abnormal MoCA scores within each group and in all groups. Results are shown in table 1 . In patients with an AI-CTD, the cognitive function assessed wasnt associated to any of the immune-related but associated with the presence of a cardiovascular risk factor (p=0.04) while CD was associated with anxiety and depression in at risk individuals (p=0.047). A relationship between CD and level of education, gender and current work was also observed. Conclusions: In this exploratory study we identified an association between conventional cardiovascular risk factors and cognitive dysfunction. However there was no association between any of the immune parameters and MoCA score. Prevention of cognitive dysfunction in SLE should focus on early identification and treatment of cardiovascular risk. Funding Source(s): None References: Md Yusof, et al. ARD 2018. El-Sherbiny, et al. Sci Rep 2018.